The effects of short-term mindfulness-based group intervention utilising a school setting for Japanese adolescents with trauma. Issue 2 (17th December 2021) - Ito, Daisuke; Kubo, Yuki; Takii, Ayako; Watanabe, Asuka; Ohtani, Tetsuhiro; Koseki, Shunsuke
Abstract: The use of mindfulness as a tool to improve mental health has received increased attention. Schools provide ideal environments for short-term prevention and skill development for mental health. Further, teachers can promote and reinforce students' daily use of mindfulness. This study explored the effects of a short-term group mindfulness-based intervention on the mental health of adolescents who have experienced trauma. A total of 49 high school students received a mindfulness-based intervention session followed by homework and teacher reinforcement. The results suggest that a short-term group intervention for mindfulness can potentially improve mindfulness attention awareness and reduce depression and anxiety symptoms in adolescents. As there was no control group, additional research examining the effectiveness of the intervention is essential.